IMPACTS OF THE NEW 2017 ACC/AHA HYPERTENSION GUIDELINE ON THE PREVALENCE OF BRACHIAL HYPERTENSION AND ITS CONCORDANCE WITH CENTRAL HYPERTENSION. (June 2018) - Chen, C.H.; Chuang, S.Y.; Cheng, H.M.; Chang, H.Y.; Pan, W.H.
Abstract : Objective: The new 2017ACC/AHA hypertension guideline lowers the criteria for diagnosing high blood pressure (BP) and will certainly increase the burden of hypertension control. We therefore aimed to investigate how the new guideline influences the prevalence of brachial hypertension and whether the newly defined brachial hypertension improves the prediction of central hypertension in an Asian nationally representative population. Design and method: A total of 2742 adults older than 19 years participated in the 2013–2016 National Nutrition and Health Survey in Taiwan. Central and brachial BP were simultaneously measured using a cuff-based stand-alone central BP monitor purporting to measure invasive central BP (Type II device). Brachial hypertension was defined by the new criteria of brachial systolic/diastolic BP >  = 30 or 80 mm Hg or using anti-hypertensive medications, and central hypertension was defined by central systolic/diastolic BP >  = 130 or 90 mmHg or using anti-hypertensive medications. Results: The national weighted prevalence rates of brachial hypertension with new AHA/ACC guideline were 48.7% in men and 30.4% in women. The prevalence of brachial hypertension increased by 18.8% in men and 9.1% in women, when compared with the prevalence defined by conventional criteria of brachial systolic/diastolic BP >  = 140 or 90 mm Hg or using anti-hypertensive medications. The increased prevalence of brachial hypertension was due to high diastolic BP (> = 80 mmHg), high systolic BP (> = 130 mmHg), and both in 47%, 24% and 29% of men, and in 33%, 44% and 23% of women. In comparison with the conventional criteria, the new hypertension criteria had a highersensitivity (93.0% vs. 77.4%), a lower specificity (86.7% vs. 99.6%), and a lower concordance (0.76 vs. 0.82)for detecting the central hypertension. Conclusions: Almost half of men and one-third of womenwould be identified as having brachial hypertension bythe new AHA/ACC guideline. The increased prevalence of brachial hypertension was mainly attributed to the new diastolic BP criterion in men and the new systolic BP criterion in women. The new hypertension criteria would not improve the concordance between brachial and central hypertension.